Implementasi Teknologi dalam Pendidikan Ekologi untuk Meningkatkan Pemahaman Siswa tentang Isu Lingkungan Global: Review - Onny, Fariha (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to review the implementation of technology in ecology education as an effort to improve students' understanding of global environmental issues. In recent decades, technological developments have opened up new opportunities in the learning process, including in the field of environmental education. Through a literature review, this study identifies various forms of technology used in ecology learning, such as mobile-based applications, computer simulations, website-based learning, and the use of social media to increase environmental awareness. The results of the review indicate that technology has great potential in enriching students' learning experiences, facilitating more interactive learning, and increasing student engagement in global environmental issues. The implementation of this technology also faces various challenges, such as the gap in technology access and the need for the development of relevant and effective materials. This study concludes that technology can be an effective tool to improve students' understanding and participation in preserving the environment, but the right strategy is needed in its utilization in order to overcome existing obstacles.